CARPAL TUNNEL SYNDROME (CTS) FOR WORKERS USING COMPUTER IN THE FINANCE DIVISION OF PROPERTY INDUSTRY - Sulistika, Nevi; Kusumaningtiar, Devi Angeliana; Handayani, Putri; Situngkir, Decy; Anggara, Taufik Rendi (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: One of the occupational diseases is Carpal Tunnel Syndrome (CTS). CTS is a condition in which the hand feels tingling, numb, painful, or weak. This syndrome occurs when the nerves inside the wrist are squeezed or compressed. Jobs that are at risk of CTS involve doing repetitive movements, working with awkward postures, working in a motorized vehicle production or working using computers. Purpose: To determine the factors associated with the incidence of CTS in workers that used computers in the finance division of Property Industry. Method: This research used quantitative research with cross-sectional design with a total sample of 34 respondents who worked in the finance division. The data were obtained through secondary data and questionnaires with direct observation and variables including gender, age, length of service, working period and awkward hand postures. The analysis carried out includes univariate and bivariate analyses using the chi-square test. Result: The univariate analysis of the respondents indicated there were 22 people (68.8%) experiencing CTS. Further, there were 22 people (75.5%) at risk from gender proportion, 22 people (68.8%) from age, 26 people (81.3%) from length of service, 22 people (68.8%) from long working period, and 24 people (74.0%) from awkward postures. Conclusion: There is a relationship between length of service, posture and the incidence of CTS on the workers using computers from the financial division of Property Industry.